1989
DOI: 10.1071/rj9890015
|View full text |Cite
|
Sign up to set email alerts
|

Soil surface features as indicators of rangeland site productivity.

Abstract: Criteria for the classification of Red Earth soils into groups reflecting differences in their productive potenrial were investigated on three sites near Cobar, New South Wales. Five features were shown to be useful by cluster and discriminate analysis of an extensive data set. A field-based classification using six very similar criteria was also tested and shown to agree with the cluster method. Laboratory tests for stability and fertility of the surface soil layer from each class indicated a significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…In that study, biomass of biennial grasses and forbs increased as the cover of microbiota increased. Similarly, Tongway and Smith (1989) showed that a high degree of microbiotic cover and diversity on red earth soils was associated with highly productive sites, i.e. high biomass.…”
Section: Interactions With Vascular Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that study, biomass of biennial grasses and forbs increased as the cover of microbiota increased. Similarly, Tongway and Smith (1989) showed that a high degree of microbiotic cover and diversity on red earth soils was associated with highly productive sites, i.e. high biomass.…”
Section: Interactions With Vascular Plantsmentioning
confidence: 99%
“…Tongway and Smith (1989) developed a field-based methodology to classify the surface condition of red earth soils in the semi-arid woodlands of eastern Australia. This system reflects differences in the erosional status, nutrient status and stability of the soil surface (Tongway and Smith 1989).…”
Section: Ground-based Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Early efforts to classify soil surfaces and include biological soil crusts were developed in the semi-arid woodlands of eastern Australia (Tongway and Smith 1989). This assessment showed differences in the stability, erosion, and nutrient status of soil surfaces, and provided a reliable estimate of potential productivity of the surface independent of vascular NOTES vegetation.…”
Section: Monitoring Methodsmentioning
confidence: 99%
“…Existing methods of mapping cryptobiotic crusts are generally implemented by visual techniques-soils are inspected in the field and several classes of development are distinguished from one another according to established protocols (for example, Tongway and Smith, 1989;Belnap and others, 2001). The areal extent of cryptobiotic crust at a particular site can be mapped directly on a photographic base map, such as a low-altitude orthophotograph, or can be mapped by survey boundary methods, such as GPS or total station.…”
Section: Detection and Mapping Of Cryptobiotic Soil Crustmentioning
confidence: 99%